-9m+45-3(m-4)=8m-(7m-4)+18

Simple and best practice solution for -9m+45-3(m-4)=8m-(7m-4)+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9m+45-3(m-4)=8m-(7m-4)+18 equation:


Simplifying
-9m + 45 + -3(m + -4) = 8m + -1(7m + -4) + 18

Reorder the terms:
-9m + 45 + -3(-4 + m) = 8m + -1(7m + -4) + 18
-9m + 45 + (-4 * -3 + m * -3) = 8m + -1(7m + -4) + 18
-9m + 45 + (12 + -3m) = 8m + -1(7m + -4) + 18

Reorder the terms:
45 + 12 + -9m + -3m = 8m + -1(7m + -4) + 18

Combine like terms: 45 + 12 = 57
57 + -9m + -3m = 8m + -1(7m + -4) + 18

Combine like terms: -9m + -3m = -12m
57 + -12m = 8m + -1(7m + -4) + 18

Reorder the terms:
57 + -12m = 8m + -1(-4 + 7m) + 18
57 + -12m = 8m + (-4 * -1 + 7m * -1) + 18
57 + -12m = 8m + (4 + -7m) + 18

Reorder the terms:
57 + -12m = 4 + 18 + 8m + -7m

Combine like terms: 4 + 18 = 22
57 + -12m = 22 + 8m + -7m

Combine like terms: 8m + -7m = 1m
57 + -12m = 22 + 1m

Solving
57 + -12m = 22 + 1m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
57 + -12m + -1m = 22 + 1m + -1m

Combine like terms: -12m + -1m = -13m
57 + -13m = 22 + 1m + -1m

Combine like terms: 1m + -1m = 0
57 + -13m = 22 + 0
57 + -13m = 22

Add '-57' to each side of the equation.
57 + -57 + -13m = 22 + -57

Combine like terms: 57 + -57 = 0
0 + -13m = 22 + -57
-13m = 22 + -57

Combine like terms: 22 + -57 = -35
-13m = -35

Divide each side by '-13'.
m = 2.692307692

Simplifying
m = 2.692307692

See similar equations:

| n-5=-9+3n | | -4x-5(-x-9)=39 | | 2(y-5)-2x-y=7 | | 2X-3/4=-1/10 | | X=2x^2-5x+2 | | 13-4=6 | | 2(x-4)=3(x-1) | | 2a-4=10a | | 5a+3+6a-12+90=180 | | 11-5=5 | | .7(200-x)=126 | | 7(y+4)=3y-8 | | x+50=180 | | 8[4-(-4x-9)]=64x+176 | | .7(200-x)=133 | | solve(2+4)(2-2)=-5 | | 3(12-5)^2/(4+3) | | -2.1q-1=6.6 | | -4U+3/2=7/2U-1/5 | | 4+2x+15=x+13 | | 12x+25=29 | | 5a+3+6a-12=180 | | 4.7+3g=7.3 | | sqrt(5-x)+1=x-2 | | 4.2(x+8.7)=8.7x | | -4-n-4=-11 | | 6-x=37 | | 12x-1+3=7x+1 | | 3a/2+1=18 | | 22/5d*10/2 | | 3-4q=10+10 | | 3a+6+4a=-36 |

Equations solver categories